Basic physics - Kuhn, Karl F. (New York : J. Wiley, 1996)
A guide to understanding physics, reviewing such physical phenomena as energy, sound, electricity, light, and color, and includes a self-test at the end of each chapter.
Includes index.
Appraisal-Science Books for Young People.
Young Adult
Keywords: Physics; Physics